Exploring the potential prompting role of cervical human papilloma virus detection in vulvar lesions: a cross-sectional study in China - Dang, Xiaoqing; Lu, Quanlong; Li, Jing; Li, Ruifang; Feng, Bo; Wang, Chen; Gao, Lifang; Feng, Ruimei; Wang, Zhilian (Frontiers in Oncology, 2024)
Introduction The etiology and clinical presentation of vulvar carcinomas, especially vulvar lesions, are not fully understood. Because the vulva and cervix are anatomically connected, human papillomavirus (HPV) is the main cause of cervical lesions. Thus, this study explored the potential characteristics and effects of specific HPV infection types across vulvar lesions and concurrent cervical lesions. Methods This retrospective, cross-sectional study analyzed patients with cervical HPV or cytological results and concurrent vulvar biopsy who were seen in our hospital colposcopy clinic in Shanxi Province, China, between 2013 and 2023. Data on age, menopause status, vulvar manifestations, and cytology and HPV infection testing results were collected. Attributable fractions and multinominal logistic models were used to evaluate HPV genotyping and clinical characteristics across vulvar lesions. Results Among the 1,027 participants, 83 (8.1%) had vulvar intraepithelial neoplasia (VIN) of high grade or worse (VIN2+), and 127 (12.4%) had non-neoplastic epithelial disorders of the vulva (NNEDV). A total of 175 patients had either VIN2+ or cervical intraepithelial neoplasia (CIN) lesions of grade 2 or worse (CIN2+). The most common HPV genotypes for VIN2+ or concurrent VIN2+/CIN2+ were HPV16, HPV52, and HPV58, although attributable fractions differed among lesions. Patients with normal cytological or histopathological result were more likely to have NNEDV detected, while abnormal cervical diagnosis was associated with higher detection of VIN2+. Multinominal logistic modeling showed that age and HPV16 infection were risk factors for VIN2+ or concurrent VIN2+/CIN2+; however, only vulvar presentation with depigmentation was a risk factor for NNEDV. Among patients with low-grade CIN1/VIN1, compared with those who were HPV16 negative, those who were HPV16 positive were at 6.63-fold higher risk of VIN2+/CIN2+ [95% confidence interval (CI): 3.32, 13.21]. Vulvar depigmentation was also associated with increased risk of NNEDV (odds ratio: 9.98; 95% CI: 3.02, 33.04). Conclusions Chinese women may be at specific, high risk for HPV infection types associated with VIN or CIN. The use of cervical cell HPV detection along with vulvar presentation during cervical cancer screening may also contribute to vulvar lesion detection.